(Removed) Effect of Growth Regulator on Regeneration of Two Sweet Potatoes (Ipomoea batatas L.) - Kamal, MM (Journal of Environmental Science and Natural Resources, 2015)
17th February 2015. Due to an editorial error, this article was duplicated by mistake in this issue. The correct version of the article is on pages 113-116 (DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22156)